PENGARUH SUKU BUNGA DEPOSITO, PRODUK DOMESTIK BRUTO (PDB) PERKAPITA DAN KURS TERHADAP OBLIGASI RITEL INDONESIA (ORI) - Aritonang Maringan; Rosyetti Rosyetti; Widayatsari Any (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Indonesian Retail Bonds or commonly referred to as ORI is the state bondsissued by the Indonesian government that is sold to private persons or individualscitizens of Indonesia through a selling agent. With the aim of expanding theinvestor base in the country, as an alternative investment instruments to retailinvestors, to support the stability of the domestic financial market, support thecreation of community oriented mid and long-term investment, and realize theideals of self reliance in development financing. Bond investors are in greatdemand because it is safe (low risk). However, in addition to seeking safe,investors also expect a maximum return. This study aims to analyze how depositrates, per capita gross domestic product, and exchange rate affect the IndonesianRetail Bonds demand. The types of data used in this study was a time series datafrom 2006 to 2018 which were sourced from Bank Indonesia and Badan PusatStatistik. This study used quantitative research methods, and analyzed by usingmultiple linear regression analysis by using EViews 10 software program forWindows computers. The result showed the variable Deposito Interest Rate, PerCapita Gross Domestic Product, and Exchange Rate at once / simultaneously hada significant influence on Indonesian Retail Bonds Demand. The individual test /partial showed that Per Capita Gross Domestic Product and Exchange Rate hadpositive influence and significantly on Indonesian Retail Bonds Demand. WhileDeposito Interest Rate had negative influence and significantly on the demand forIndonesian Retail Bonds. Ability prediction of independent variable to explain thedependent variabel with value of adjusted R square equal 0,950919. This meanthat total effect from three independent variabel to dependent variabel is 95.1%while the remaining 4,9% is explained by other variables not included in thisstudy.Keyword : Indonesian Retail Bonds, Deposit Rate, Gross Domestic Product, andExchange Rate.